Redescription of Echinolaophonte armiger (Gurney) (Copepoda: Harpacticoida) from the Gulf of Mexico - Lee, Wonchoel; Soh, Ho Young; Montagna, Paul A. (Zootaxa, 2006)
Echinolaophonte armiger (Gurney, 1927) is redescribed from the Texas coast (Gulf of Mexico). The species has a simple but strong dorsal spinous process on the cephalosome and the pairs of minute, spiny processes along the posterodorsal margins of the prosomites and urosomites. This is the first full description of the species since Gurney’s (1927) original report from the Suez Canal. The previous reports of E. armiger are reconsidered based on new morphological characters revealed in the present study. As a result, Echinolaophonte hystrix (Brian, 1928) is revived as a valid species, and the status of closely related species, formerly known as E. armiger, is also discussed.